The Relationship Between Challenging Behaviour, Cognitions and Stress in Mothers of Individuals with Intellectual Disabilities. Issue 6 (22nd June 2016) - Rose, John; Nelson, Lisa; Hardiman, Rebecca
Abstract : Background: Cognitions are starting to receive more prominence as important when examining a number of factors including the topography of challenging behaviour. This study examined the relationships between maternal stress, challenging behaviour (aggressive and self-injurious behaviours) and parental cognitions and specifically whether maternal cognitions mediated the effect of challenging behaviour on parenting stress.Method: 46 mothers of children and young adults with ID completed questionnaires regarding their child's challenging behaviour, maternal cognitions and stress.Results: Significant correlations were found between challenging behaviour and maternal stress. The overall mediation models for aggression and self-injurious behaviour were significant. The Challenging Behaviour Perception Questionnaire: Consequences client subscale was the only independent significant mediator for both behaviours.Conclusions: Cognitions do play an important part in mediating the relationship between challenging behaviour and stress. Further research is needed to examine the similarities and differences between the mediation models for aggression and self-injurious behaviour.